Efficacy of novel allogeneic cancer cells vaccine to treat colorectal cancer - Alzeeb, George; Tortorelli, Corinne; Taleb, Jaqueline; De Luca, Fanny; Berge, Benoit; Bardet, Chloé; Limagne, Emeric; Brun, Marion; Chalus, Lionel; Pinteur, Benoit; Bravetti, Paul; Gongora, Céline; et al. (Frontiers in Oncology, 2024)
Colorectal cancer (CRC) remains a significant global health burden, emphasizing the need for innovative treatment strategies. 95% of the CRC population are microsatellite stable (MSS), insensitive to classical immunotherapies such as anti-PD-1; on the other hand, responders can become resistant and relapse. Recently, the use of cancer vaccines enhanced the immune response against tumor cells. In this context, we developed a therapeutic vaccine based on Stimulated Tumor Cells (STC) platform technology. This vaccine is composed of selected tumor cell lines stressed and haptenated in vitro to generate a factory of immunogenic cancer-related antigens validated by a proteomic cross analysis with patient’s biopsies. This technology allows a multi-specific education of the immune system to target tumor cells harboring resistant clones. Here, we report safety and antitumor efficacy of the murine version of the STC vaccine on CT26 BALB/c CRC syngeneic murine models. We showed that one cell line (1CL)-based STC vaccine suppressed tumor growth and extended survival. In addition, three cell lines (3CL)-based STC vaccine significantly improves these parameters by presenting additional tumor-related antigens inducing a multi-specific anti-tumor immune response. Furthermore, proteomic analyses validated that the 3CL-based STC vaccine represents a wider quality range of tumor-related proteins than the 1CL-based STC vaccine covering key categories of tumor antigens related to tumor plasticity and treatment resistance. We also evaluated the efficacy of STC vaccine in an MC38 anti-PD-1 resistant syngeneic murine model. Vaccination with the 3CL-based STC vaccine significantly improved survival and showed a confirmed complete response with an antitumor activity carried by the increase of CD8+ lymphocyte T cells and M1 macrophage infiltration. These results demonstrate the potential of this technology to produce human vaccines for the treatment of patients with CRC.